Pedagogic Task BasedActivity to Develop Students’ Intercultural Communicative Competence - Widyaningrum, Agnes; Saleh, Mursid; Warsono, Warsono; Sutopo, Djoko (The Journal of Educational Development, 2018)
TEFL in Indonesia is conducted on the framework of improving student’s cognitive and psycho-motoric but less in affective activity. The shift from foreign language to multicultural language (Honna, 2000, 2003) is to build intercultural awareness (2008, p.72). In school pedagogic activity is designed to accessing its modes of implementation, its operation and its outcome (Leung, 1993). It emphasizes on the process thus reflection is beyond the focus. Textbook is made on the basis of CLT with the aim to teach communicative competence (Richards, 2006, p.2) by implementing Task Based Approach focusing on creating kinds of interactional processes in the classroom (2006, p.30). ICC is the goal of TEFL therefore an innovation is made to develop student’s ability to be socially and culturally competent speakers (Byram, 2001). The findings show that pedagogic task based adopted authentic as well as created situation and cultural values can boost student’s ICC.